The Quality of Training Future Teachers during the COVID-19 Pandemic: A Case from TNPU - Mariya Boyko; Olha Turko; Oleksandr Dluhopolskyi; Halyna Henseruk (MDPI AG, 2021)
This article describes the experience of the communicative competence formation of future teachers in a blended form of education as a dominant one in the period of the COVID-19 pandemic. The main features of such terms as "education quality" and "communicative competence" are revealed; the peculiarities of their components and structure are described. Using the results of a survey the authors draw conclusions about the advantages and disadvantages of online and offline learning and the efficacy of technical learning tools. The article also describes the educational platforms and technical means most frequently used by teachers and students in their everyday life. The results of testing in philological and linguodidactic disciplines after online and offline learning are presented in the paper. Conclusions are made concerning the peculiarities of online and offline training by means of Moodle and Google Classroom learning platforms, as well as Viber, Telegram, Email, Zoom Cloud Meetings and other platforms. Considering the results of the survey of students on the usage of technical means in online learning, the authors provide suggestions on improving the quality of training future teachers. The discussion part of the article presents the questions for discussion concerning a blended form of training as an effective one during the COVID-19 pandemic. The conclusion states the advantages and disadvantages of mixed forms of learning.